DAMPAK KOMODIFIKASI TERHADAP PERUBAHAN IDENTITAS TARI TOPENG HITAM - Tessaniva Agusta; Warto Warto; Supana Supana (Universitas Sebelas Maret, 2017)
This Study discuss the impact of co-modification of topeng hitam dance as cultural attraction in Ngrawan Village Semarang Regency The results show that co-modification has been taken place since 2012 which was done by the parties concerning with the development of topeng hitam dance which is potential to be a cultural tourism asset. Consequently, it will, economically, give benefits to the people of Semarang Regency; especially for people of Ngrawan Village where the dance originated from, and also, the local tourism agencies. However, despite the beneficial fact in the tourism sector, the co-modification process devastates the historical values and the value of identity of topeng hitam dance due to the commercialization.